Enantioselective Synthesis of Dihydropyrazoles by Palladium/Xu‐Phos‐Catalyzed Alleneamination of β,γ‐Unsaturated Hydrazones with Propargylic Acetates - Zhang, Shuting; Wu, Shuaijie; Wang, Qiang; Xu, Shiji; Han, Ying; Yan, Chao‐Guo; Zhang, Junliang; Wang, Lei (Angewandte Chemie International Edition, 2023)
The palladium‐catalyzed asymmetric carboamination reaction is one of the most significant transformations in organic chemistry. Herein, we report the first palladium‐catalyzed asymmetric alleneamination of β,γ‐unsaturated hydrazones with propargylic acetates. This protocol enables the efficient installation of various multisubstituted allene groups onto dihydropyrazoles in good yields with excellent enantioselectivities. The chiral sulfinamide phosphine ligand Xu‐5 exhibits highly efficient stereoselective control in this protocol. The salient features of this reaction include the readily available starting materials, a broad substrate scope, an easy scale‐up, mild reaction conditions and versatile transformations. A new robust palladium‐catalyzed enantioselective alleneamination reaction of β,γ‐unsaturated hydrazones with propargylic acetates is described. The salient features of this reaction include general substrate scope, good functional group tolerance, good yields and high enantioselectivities.